Transformasi Kebijakan Kurikulum di Indonesia dalam Perspektif Filsafat Pendidikan: Analisis Kritis dan Implikasinya terhadap Praktik Pembelajaran - Mus S. Radjilun (CV Cendekia Paramartha, 2026)
This study aims to analyze the transformation of curriculum policy in Indonesia from the perspective of educational philosophy and its implications for learning practices. The research employs a non-empirical approach using a critical literature review based on academic sources and policy documents. The findings indicate that curriculum transformation is characterized by a shift from a humanistic paradigm toward the integration of constructivism, critical theory, and posthumanism. While this integration expands educational orientation, it remains conceptually fragmented and generates inconsistencies in policy implementation. These issues are reflected in diverse learning practices, including changes in teacher roles, the emergence of participatory learning, and the integration of digital technology. However, limited philosophical understanding and systemic readiness hinder optimal implementation. The study highlights the necessity of systematic philosophical reconstruction in curriculum policy to ensure coherent and contextually relevant educational transformation. This research contributes to bridging the gap between educational philosophy and curriculum policy through a critical and integrative analytical framework.